Maxis Communications Berhad: Maintaining Dominance In The Malaysian Mobile Communications Industry - Abang Zainal Abidin, Dayang Nuryati (2004)
Maxis has been successfully building its brand name and achieving profitable growth through a value proposition of premium and quality in terms of brand name, network, customer services, products and services, distribution and financial management. However, as competition intensifies, Maxis faces many challenges in the current telecommunications landscape especially as there are only 3 major players in the industry.